Análise de correlação entre acidentes de trânsito, de trajeto e variáveis socioeconômicas no Brasil - Cabral, Claudio Freaza (Universidade Federal de São Carlos, 2009)
The man needs the work to satisfy their needs and the concern with the safety and the workers' health constitutes one of the most important and current problems, provoking interest to the employers, the government's agents and mainly the employees, concern that it happens in all of the industrialized countries. Investments in the prevention and knowledge on these accidents bring advantages for the companies, workers and society. And when detaching the itinerary accident, they are deficiencies of the sources of official information, where the sub-registrations dominate, impeding a reliable analysis. Also damages provoked by the accidents of traffic are one of the main problems of public health in world level, requesting combined efforts for prevention executes and maintainable. This work has as main objective to investigate possible relationships among socioeconomic and population indicators with the occurrence of the itinerary accidents, with data attachés in level of Capitals and Brazilian States (UF), seeking to subsidize united politics of safety of traffic and of work. The used methodology will be through risings, treatment and verification of consistence of the data with analyses in the capitals and Units of Federation (UF), Using tool of statistical analysis for 2005. The results can be useful, could supply subsidies for the target of actions in the extent of the system of transports, in way to minimize the imposed risks the quality of life of the population, described through the accidents of traffic.
Keywords: Acidentes de trânsito; Acidentes de trajeto; Análise estatística e correlação de Pearson; Acidente de trabalho; Work accidents; Itinerary accidents; Accidents of traffic; Statistical analysis and correlation of Pearson; ENGENHARIAS